A longitudinal online interprofessional education experience involving family nurse practitioner students and pharmacy students. Issue 2 (4th March 2017) - Collins, Andrea; Broeseker, Amy; Cunningham, Jill; Cortes, Cyndi; Beall, Jennifer; Bigham, Amy; Chang, Jongwha
ABSTRACT: Interprofessional education (IPE) continues to gain traction worldwide. Challenges integrating IPE into health profession programmes include finding convenient times, meeting spaces, and level-appropriate assignments for each profession. This article describes the implementation of a 21-month prospective cohort study pilot programme for the Master of Science in nursing family nurse practitioner (FNP) and doctor of pharmacy (PharmD) students at a private university in the United States. This IPE experience utilised a blended approach for the learning activities; these students had initial and final sessions where they met face-to-face, with asynchronous online activities between these two sessions. The online assignments, discussions, and quizzes during the pilot programme involved topics such as antimicrobial stewardship, hormone replacement therapy, human papilloma virus vaccination, prenatal counselling, emergency contraception, and effects of the Affordable Care Act on practice. The results suggested that the FNP students held more favourable attitudes about online IPE and that the PharmD students reported having a clearer understanding of their own roles and those of the other participating healthcare students. However, the students also reported wanting more face-to-face interaction during their online IPE experience. Implications from this study suggest that effective online IPE can be supported by ensuring educational parity between students regarding the various topics discussed and a consistent approach of the required involvement for all student groups is needed. In addition, given the students desire for more face-to-face interaction, it may be beneficial to offer online IPE activities for a shorter time period. It is anticipated that this study may inform other programmes that are exploring innovative approaches to provide IPE to promote effective collaboration in patient care.